APPLICATION OF BEHAVIORAL ACCOUNTING: HEURISTIC THINKING IN INVESTMENT DECISION-MAKING BY CRYPTOCURRENCY INVESTORS - Jonnie, Jonnie; Soeherman, Bonnie (Ridwan Institute, 2024)
This study aims to examine the impact of heuristic involvement on the behavior and decisions of cryptocurrency investors. The study employs an interpretivism paradigm with a qualitative approach to understand the perspectives of both beginner and experienced cryptocurrency investors, using interviews, observations, and document analysis. Four cryptocurrency investors participated in the study. Interviews were conducted three times a week, while observations followed a semi-structured format to gather in-depth insights from four investors. Document analysis complemented the findings by reviewing relevant literature on the impact on investment behavior. Data collection included non-participant observations of investor behavior and decision-making habits, interviews that explored the factors influencing these decisions, and an analysis of documents, including previous research on heurism biases. Heuristic representativeness is a useful tool to predict the development of cryptocurrencies in the long term to a certain extent.